Effect of seaweed Kappaphycus alvarezii in the synthesis of Cu@Cu2O core–shell nanoparticles prepared by chemical reduction method - Khanehzaei, Hajar; Ahmad @ Ayob, Mansor; Shameli, Kamyar; Ajdari, Zahra; Abd Ghani, Maaruf; Kalantari, Katayoon (Springer, 2015)
This study aims is to investigate the influence of different concentrations of Kappaphycus alvarezii (K. alvarezii) for the synthesis of Cu@Cu2O core–shell nanoparticles (NPs) in aqueous solution. The core–shell NPs were prepared by a chemical reduction method using K. alvarezii, CuSO4·5H2O, NaOH, ascorbic acid, hydrazinium hydroxide, as stabilizer, copper precursor, pH moderator, antioxidant and reducing agent under 120°C temperature, respectively. Formation of Cu@Cu2O-NPs was determined by UV–Vis spectroscopy where surface plasmon absorption maxima can be observed at 390-590 nm. The synthesized core–shell NPs were also characterized by X-ray diffraction. Moreover, the morphology and structure of the K. alvarezii/Cu@Cu2O-NPs were investigated by TEM, FESEM and EDXRF. The Fourier transform infrared spectrum suggested the complexation present between K. alvarezii and Cu@Cu2O-NPs. The study clearly showed that using various amounts of K. alvarezii leads to produce different ratios and sizes of Cu@Cu2O NPs. The size of the Cu@Cu2O-NPs decreased as the amount of K. alvarezii was increased. The ratio of Cu@Cu2O increases with the increasing concentration of K. alvarezii until 0.2 wt%.